2006
DOI: 10.1039/b610810e
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectropolymerization of aniline in a dye-sensitized solar cell

Abstract: A dye-sensitized solar cell was constructed using a porphyrin photosensitizer and, in place of the usual iodide redox system, a solution in aniline solvent containing lithium perchlorate electrolyte, camphorsulfonic acid, and poly(ethylene oxide) copolymer. Irradiation generated polyaniline within the cell, initially following a proposed photoelectropolymerization mechanism, and eventually operating as a solar cell with polyaniline as the hole transport medium. Overall energy conversion efficiency was 0.8% at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Therefore the polymerization can directly start at the dye molecule itself, bringing the dye and the hole-transporter polymer into close molecular contact. Such close contact was proven to be beneficial in terms of photoelectrochemical behavior, compared to a counterpart using a dye without monomeric moieties [232][233][234][235][236].…”
Section: Figure 14mentioning
confidence: 97%
“…Therefore the polymerization can directly start at the dye molecule itself, bringing the dye and the hole-transporter polymer into close molecular contact. Such close contact was proven to be beneficial in terms of photoelectrochemical behavior, compared to a counterpart using a dye without monomeric moieties [232][233][234][235][236].…”
Section: Figure 14mentioning
confidence: 97%
“…More recent work has studied mixed amino/carboxyphenylporphyrins, using the amino groups as possible nucleation points for polymerization of aniline to create solid-state solar cells [118]. Using 5-(4-aminophenyl)-10,15,20-tris(4-carboxyphenyl)porphyrin in a liquid electrolyte solar cell with a polyaniline counter electrode gave an overall efficiency of 1.1% [119]. The ability to create a variety of substituents on the porphyrin macrocycle has become very popular with the advent of simple synthetic methodology to meso tetrasubstituted porphyrins [120].…”
Section: Porphyrins In Dsscsmentioning
confidence: 99%
“…1 These planar, π-conjugated macrocycles commonly find widespread use as the semiconducting layer in field effect transistors, [2][3][4] organic light emitting diodes 5 and as the light harvesting component in solar cells. 6,7 An attractive feature is the ability to functionalise the periphery and/or incorporate a wide range of metal ions into the central cavity of these macrocycles, in order to tune their physical, optical and electronic properties. In addition to its electronic effect, it has previously been demonstrated that the size of the central metal ion can play a key role in the charge carrier mobility, by dictating the intermolecular distance in the crystal lattice, 8 with the smaller metal facilitating better overlap of the ligand based frontier orbitals.…”
Section: Introductionmentioning
confidence: 99%